2020
DOI: 10.1002/we.2464
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different forest densities on atmospheric boundary‐layer development and wind‐turbine wake

Abstract: The aim of this work is to investigate the atmospheric boundary-layer (ABL) flow and the wind turbine wake over forests with varying leaf area densities (LAD). The forest LAD profile used in this study is based on a real forest site, Ryningsnäs, located in Sweden. The reference turbine used to model the wake is a well-documented 5-MW turbine, which is implemented in the simulations using an actuator line model (ALM). All simulations are carried out with openFOAM using the Reynolds averaged Navier-Stokes (RANS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…The impact of forests depends on the size, the height of the trees, and the forest density (LAI) (Adedipe et al, 2022). Previously, it has been seen that a dense homogeneous forest can increase the turbulence level by 4-5 times above the forest edge compared to a no-forest case (Nebenführ & Davidson, 2014;Adedipe et al, 2020). This is in agreement with our results.…”
Section: Forest Density and Turbulencesupporting
confidence: 93%
See 2 more Smart Citations
“…The impact of forests depends on the size, the height of the trees, and the forest density (LAI) (Adedipe et al, 2022). Previously, it has been seen that a dense homogeneous forest can increase the turbulence level by 4-5 times above the forest edge compared to a no-forest case (Nebenführ & Davidson, 2014;Adedipe et al, 2020). This is in agreement with our results.…”
Section: Forest Density and Turbulencesupporting
confidence: 93%
“…The approach used here to model the forests has been successfully used in several studies previously (Finnigan et al, 2009;Desmond & Watson, 2014;Agafonova et al, 2016aAgafonova et al, , 2016bAdedipe et al, 2020Adedipe et al, , 2022 and it has been validated against measurements (Chaudhari et al, 2016a;Adedipe et al, 2020).…”
Section: Numerical Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…They observed a higher rate of energy dissipation for turbulent flows in forest areas. As for the effects of forests on the wake of a wind turbine, Adedipe et al [32] found that the presence of forests accelerates the recovery of wind turbine wakes for different leaf area densities (LADs) using the Reynolds-Averaged Navier-Stokes (RANS) method. Cheng et al [33] investigated the influence of different forest densities on the wake of a model wind turbine and showed that the forest canopy had a significant modulation effect on the wind turbine wakes via a quadrant analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Early this century, the AL model and the AS model are proposed respectively as the improvement of the AD model. Among them, the AL model is widely used in engineering because of its good precision and acceptable computation cost [28,29,30].…”
Section: Introductionmentioning
confidence: 99%